Pulmonary O2 uptake during exercise: Conflating muscular and cardiovascular responses - Whipp, B. J.; Ward, S. A.; Rossiter, H. B. (Medicine & Science in Sports & Exercise, 2005)
For moderate-intensity exercise (below lactate threshold, [theta]L), muscle O2 consumption (QO2) kinetics are expressed in a first-order phase 2 (or fundamental) pulmonary O2 uptake (VO2) response: dVO2/dt [middle dot] [tau] + [DELTA]VO2(t) = [DELTA]VO2(ss); where [DELTA]VO2(ss) is the steady-state VO2 increment, and [tau] the VO2 time constant (which is within approximately 10% of [tau]QO2). A likely source of QO2 control in this intensity domain is ADP-mediated, for which intramuscular phosphocreatine (PCr) may serve as a proxy variable. Whether, in reality, this behavior reflects the operation of a single homogeneous compartment is unclear, however; a multicompartment structure comprised of units having a similar [DELTA]VO2(ss) but with widely varying [tau] can also yield a "well-fit" exponential response with an apparent single [tau]. In support of this is the inverse (although poorly predictive) correlation between [tau] and both [theta]L and VO2max. Above [theta]L, the fundamental VO2 kinetics are supplemented with a delayed, slowly developing component that can set VO2 on a trajectory towards VO2max, and that has complex temporal- and intensity-related kinetics. This VO2 slow component is also demonstrable in [PCr], suggesting that the decreased efficiency above [theta]L predominantly reflects a high phosphate cost of force production rather than a high O2 cost of phosphate production. In addition, the oxygen deficit for the slow component is more likely to reflect a progressive shifting of [DELTA]VO2(ss) rather than a single [DELTA]VO2(ss) having a single [tau].